Winter Wheat Yield Gaps and Patterns in China. (1st January 2018) - Sun, Shuang; Yang, Xiaoguang; Lin, Xiaomao; Sassenrath, Gretchen F.; Li, Kenan
Abstract : Core Ideas: Based on yield gap analysis, wheat yield can be improved significantly in China. Both actual and potential wheat yields showed considerable spatial variability. Winter wheat yields increased in 53% of the counties in China. Nearly half of the counties experienced impaired wheat yields. Declining solar radiation and increasing temperature reduce wheat yield. Wheat ( Triticum aestivum L.) yield stagnation has been reported in some regions of the world. China is the largest producer of wheat across the globe, but the pattern of its wheat yield stagnation remains poorly addressed. Here, our goal is to examine the temporal trends and spatial patterns of wheat yields along with possible causes based on a comprehensive assessment of winter wheat yield throughout China over the 31‐yr period from 1980 to 2010. Combined with the Agricultural Production Systems Simulator (APSIM) wheat model, we assessed the winter wheat yield gaps and patterns in 1414 counties and at five physiogeographic regional scales across China to ascertain the driving factors of yield variations. Wheat yields increased in 53% of the 1414 counties, but the remaining counties experienced yields that never improved, stagnated, or collapsed from 1980 to 2010. The yield gap analysis showed that actual yields represented only 59% of the national average yield potential, indicating a substantial opportunity to improve winter wheat yields. Relatively larger yield gaps were observed in the northern China Plain (NC, 47%) and in southwestern China (SW, 45%). Although the yield gaps in these regions were accompanied by significantly progressive uptrends of actual yields, our results suggest that agronomic management could be further improved. Moreover, underperforming regions could potentially benefit from new investments and strategies to reliably increase actual yields and reverse trends in stagnation in winter wheat performance.